Relationship between Radiographic Evaluation with Age and Gender – A Radiographic Study - Nor Syakirah Binti Shahroom1, Gheena.S2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Forensic odontology plays an important role in identification of man-made or natural disasters event which restricts identification through conventional methods. Various approaches have been specified which helps in the identification of the post-mortem remains. One such is the identification of the morphological features of the human skull and mandible. These features may help in sex differentiation. The aim of this study is to evaluate the relationship between radiographic evaluation with age and gender.Materials and Method: A retrospective study was done with a total of 250 panoramic radiograph image. The images of 150 males and 100 females were selected with the range of age from 20 to 70 years old and divided into group 1 (20-45 years old) and group 2 (46-70 years old). Three parameters were evaluated from the panoramic radiograph which were gonial angle, antegonial angle and mental foramen against the age and gender. Statistical analysis was done for hypothesis testing.Results: The results of this study suggests that there is no significant difference seen in the gonial angle and antegonial angle with relation to the age (p?0.05). However, the relationship between age and mental foramen is highly significant (p?0.01). With regards to gender, all the three parameter shows highly significant results with (p?0.01).Conclusion: In conclusion, the three parameter assessed in this study can be used for gender differentiation but not for age estimation which were highly significant. As for age estimation, the distance of mental foramen and tangent line of inferior border of mandible can be assessed.